Market reaction do sports sentiment: evidence on 2008 European football championship - Vieira, Elisabete F. Simões
This paper examines whether investor sentiment influences the stock price response to football matches results. We focus on the market stock price reaction to 2008 European Football Championship. Our results provide some evidence that football match losses are associated with a negative market reaction, suggesting that losses cause a particularly negative effect on investors’ mood. However, we find no evidence supporting a significantly difference between market reaction to football match wins and losses, which is not consistent with the inherent asymmetry between elimination wins and losses. Interestingly, we find also evidence of a negative market reaction after the football match wins. In addition, our results indicate that the market reaction is stronger for small stocks than for the large ones, which suggests that small stocks valuations are more likely to be affected by sentiment.